Mycophenolate sodium for the treatment of chronic non-infectious uveitis of childhood. Issue 8 (13th November 2015) - Doycheva, Deshka; Zierhut, Manfred; Blumenstock, Gunnar; Sobolewska, Bianka; Voykov, Bogomil; Hohmann, Johanna; Spitzer, Martin S; Deuter, Christoph
Abstract : Aim: To assess the efficacy and tolerability of mycophenolate sodium (MPS) in the therapy of children with chronic non-infectious uveitis. Methods: Retrospective analysis of 23 children with chronic uveitis, treated with MPS, with a follow-up of at least 6 months. The main outcome measures were time to uveitis reactivation and corticosteroid-sparing effect under MPS treatment. The secondary outcome measures were best-corrected visual acuity (BCVA) and treatment-related side effects. Results: From 23 patients included in the study, 2 patients had anterior uveitis, 19 had intermediate uveitis and 2 had panuveitis. The probability of reactivation-free survival after MPS initiation was estimated as 65% at both 1 and 2 years. The probability of discontinuing systemic corticosteroids after 1 year of treatment was 39% and after 2 years 51%. The probability to taper corticosteroids to a daily dosage of ≤0.1 mg/kg after 1 and 2 years was 62% and 85%, respectively. BCVA improved or remained stable in 96% of eyes after 1 year of therapy. Treatment-related side effects were found in nine children (rate: 0.17/patient-year). No therapy discontinuation because of side effects was needed. Conclusion: Our data suggest that MPS is useful and well tolerated in children with chronic uveitis. MPS seems to be an effective drug for the treatment of chronic non-infectious uveitis of childhood and may be preferred as a first-line steroid-sparing agent in this form of uveitis.